Efektivitas Penggunaan Garbarata (Aviobridge) di Bandar Udara Internasional Sultan Hasanuddin Makassar - KGS.M.Ismail; Suwono, Niedya Inten; Sari, Rafhika Indah; Labiba, Jihan Aziza; M. Alghipari; Alamsyah, Taufiq Nur (Program Studi Teknik Mekanikal Bandar Udara, 2023)
Indonesia needs effective and efficient transportation to support the needs of transportation facilities. To meet these needs, safe, fast, and comfortable transportation is needed. Passenger comfort is important for airport managers. Scheduled equipment maintenance is needed to maintain airport operational performance, maximize the maintenance and operational performance of Aviobridge, and improve service to passengers and airlines that use Aviobridge usage services. At the current Sultan Hasanuddin International Airport Makassar, the operation of the aviobridge with few Human Resources (HR) and the maintenance applied still face obstacles that do not cause the Aviobridge to not operate.